PELESTARIAN LINGKUNGAN BERBASIS PEMBERDAYAAN MASYARAKAT DI DESA MUSER KECAMATAN MUARA SAMU KABUPATEN PASER: Environment Conservation Based on Community Empowerment in Muser Village Muara Samu District, Paser Regency - Gunawan, Asril; Maiateng, Delaya Alorinda; Oktaviani, Ella; Ginting, Ica Navratilova Br; Agustina, Marini; Imka, M. Rifky; Dealyardy, Muhammad Alief; Muhajirin, Muhammad Giffar; Khoirunnisa, Salza; Rabiah, Siti; Ananda, Tasya; Hutauruk, Vida Gavrila (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2022)
Abstract: Community service activity is a concrete manifestation of KKN students in supporting aspects of the Tri Dharma of Higher Education service through environmental preservation based on community empowerment in muser villages. Community service activities in Muser Village aim to enable students to provide assistance to the community by going directly and utilizing potential resources, both natural and human resources, in the Environmental Preservation program. Environmental preservation is a work program that aims to provide education to the community on the importance of preserving the environment in the village. The activities carried out are planning work programs, coordinating with related parties such as village heads, RT heads, and other parties. The results achieved through this work program are the creation of a village environment that is healthy and clean from waste and produces seeds that can be given to every RT and schools so that they look more beautiful. Keywords: Village; environment; community; preservation. Abstrak: Kegiatan pengabdian masyarakat merupakan wujud nyata dari mahasiswa KKN dalam mendukung aspek pengabdian Tri Dharma Perguruan Tinggi melalui pelestarian lingkungan berbasis pemberdayaan masyarakat di desa muser. Kegiatan pengabdian di Desa Muser bertujuan agar mahasiswa mampu memberikan pendampingan kepada masyarakat dengan terjun langsung dan memanfaatkan potensi sumber daya baik sumber daya alam maupun manusia dalam program Pelestarian Lingkungan. Pelestarian lingkungan merupakan program kerja yang bertujuan memberikan edukasi pada masyarakat dalam pentingnya menjaga kelestarian lingkungan di desa. Adapun kegiatan yang dilakukan yakni perencanaan program kerja, melakukan koordinasi dengan pihak terkait seperti kepala Desa, ketua RT, dan pihak-pihak lainnya. Hasil yang dicapai melalui program kerja ini yaitu terciptanya lingkungan desa yang sehat dan bersih dari sampah serta menghasilkan bibit yang dapat diberikan di setiap RT maupun sekolah-sekolah agar semakin terlihat asri. Kata Kunci: Desa, lingkungan, masyarakat, pelestarian.